Effects of self-selected mass loss on performance and mood in collegiate wrestlers - Marttinen, R. H. J.; Judelson, D. A.; Wiersma, L. D.; Coburn, J. W. (The Journal of Strength and Conditioning Research, 2011)
Wrestlers abruptly lose body mass before competition; however, the effects of "weight cutting" are poorly understood because of conflicting evidence. This study aimed to determine the effects of self-selected mass loss on precompetition mood, grip strength, and lower body power in collegiate wrestlers. Sixteen male collegiate wrestlers (age = 20 ± 2 years, height = 177.5 ± 7.2 cm) were weighed 10 days before (D-10) a competitive meet. Euhydrated subjects were administered the Brunel Mood Scale (BRUMS), tested on grip strength, and given a 30-second Wingate Anaerobic Power test to determine lower body power. Additional weigh-ins were conducted 6 (D-6) and 2 (D-2) days before competition. Subjects repeated the testing battery the day of competition (D-0). During the study, wrestlers self-selected the method and timing of mass loss. Wrestlers lost 0.0-8.1% of their body mass using exercise, caloric restriction, or fluid deprivation. Most mass loss occurred between D-2 and D-0 (mean ± SD, D-10 = 81.7 ± 18.2 kg, D-6 = 81.2 ± 17.8 kg, D-2 = 81.1 ± 18.5 kg, D-0 = 79.0 ± 19.2 kg). Wrestlers losing =4% body mass became significantly more confused (D-10 = 0 ± 0, D-0 = 3 ± 3); subjects losing less mass showed no difference in confusion. No significant differences existed across time for remaining BRUMS variables, grip strength, and Wingate variables. These results suggest that wrestlers self-select large, rapid mass loss that impairs aspects of psychological functioning without affecting grip strength or lower-body power.